Comments on the Article “Management of Suspected Acute Inflammatory Pancreatopathies in a "Real-world" Setting: A Single-Centre Observational Study” - Goyal, Hemant (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Mercer University School of Medicine (Macon, GA, USA) logo.